CCR2- and Flt3-Dependent Inflammatory Conventional Type 2 Dendritic Cells Are Necessary for the Induction of Adaptive Immunity by the Human Vaccine Adjuvant System AS01 - Bosteels, Cedric; Fierens, Kaat; De Prijck, Sofie; Van Moorleghem, Justine; Vanheerswynghels, Manon; De Wolf, Caroline; Chalon, Aurélie; Collignon, Catherine; Hammad, Hamida; Didierlaurent, Arnaud M.; Lambrecht, Bart N. (Frontiers in Immunology, 2021)
The Adjuvant System AS01 contains monophosphoryl lipid A (MPL) and the saponin QS-21 in a liposomal formulation. AS01 is included in recently developed vaccines against malaria and varicella zoster virus. Like for many other adjuvants, induction of adaptive immunity by AS01 is highly dependent on the ability to recruit and activate dendritic cells (DCs) that migrate to the draining lymph node for T and B cell stimulation. The objective of this study was to more precisely address the contribution of the different conventional (cDC) and monocyte-derived DC (MC) subsets in the orchestration of the adaptive immune response after immunization with AS01 adjuvanted vaccine. The combination of MPL and QS-21 in AS01 induced strong recruitment of CD26+XCR1+ cDC1s, CD26+CD172+ cDC2s and a recently defined CCR2-dependent CD64-expressing inflammatory cDC2 (inf-cDC2) subset to the draining lymph node compared to antigen alone, while CD26-CD64+CD88+ MCs were barely detectable. At 24 h post-vaccination, cDC2s and inf-cDC2s were superior amongst the different subsets in priming antigen-specific CD4+ T cells, while simultaneously presenting antigen to CD8+ T cells. Diphtheria toxin (DT) mediated depletion of all DCs prior to vaccination completely abolished adaptive immune responses, while depletion 24 h after vaccination mainly affected CD8+ T cell responses. Vaccinated mice lacking chemokine receptor CCR2 mainly showed a marked deficit in inf-cDC2 recruitment and failed to raise proper antibody and CD4+ T cell responses. Thus the adjuvant activity of AS01 is associated with the potent activation of subsets of cDC2s, including the newly described inf-cDC2s.